2013
DOI: 10.1002/asia.201300905
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Particle Effects on Hydrate Crystal Growth at the Water–Oil Interface

Abstract: This study introduced hydrophobic silica nanoparticles (SiNPs) into an interface of aqueous and hydrate-forming oil phases and analyzed the inhibition of hydrate crystal growth after seeding the hydrate slurry. The hydrate inhibition performance was quantitatively identified by micro-differential scanning calorimetry (micro-DSC) experiments. Through the addition of 1.0 wt% of SiNPs into the water-oil interface, the hydrate crystal growth only occurred around the seeding position of cyclopentane (CP) hydrate sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…The CP hydrate slurry, a hydrate promoter, was prepared in a similar way to the method described in previous studies. 11,20,21 To make the CP hydrate slurry, 10 wt% liquid CP and 90 wt% DI water were mixed in a vial. Because the CP cannot be solubilized into DI water, the vial was shaken every 15 min to promote CP hydrate formation on the whole region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CP hydrate slurry, a hydrate promoter, was prepared in a similar way to the method described in previous studies. 11,20,21 To make the CP hydrate slurry, 10 wt% liquid CP and 90 wt% DI water were mixed in a vial. Because the CP cannot be solubilized into DI water, the vial was shaken every 15 min to promote CP hydrate formation on the whole region.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, hydrophobic silica nanoparticles were utilized as a hydrate inhibitor on cyclopentane hydrate formation with surfactant Span 80 and the inhibition effect of the silica nanoparticles on the hydrate growth was investigated with optical microscopy and micro differential scanning calorimetry (Micro-DSC). 11 The hydrophobic silica nanoparticles formed the particle layer between the oil and water phases and then they delayed or prevented the cyclopentane hydrate formation. The hydrate conversion rate and the size of the conical crystals were also reduced in the presence of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, when hydrophobic nanoparticles are at the oil-water interface, the migration of gas and liquid molecules will be prevented, thus inhibiting hydrate formation. 23,24 For hydrophilic nanoparticles, some studies have found that they can also promote hydrate formation. 25 But molecular dynamics simulations show that hydrates are difficult to form on hydrophilic solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, gas hydrate nucleation and growth is closely related to the hydrophobicity of gas, and nanoparticles can either be hydrophilic or hydrophobic. Most studies have indicated that hydrophobic nanoparticles in water system facilitate the formation of gas hydrates [25][26][27] , but they inhibit hydrate growth if they locate at the water/oil interface [28] , while other results also showed that nanoparticles facilitate the formation of hydrates at low concentrations [21,23] . However, the researchers did not elucidate the nanoparticle in their experiments is hydrophilic or hydrophobic [21,23] .…”
Section: Introductionmentioning
confidence: 99%